EFFECTS OF HYDROPRENE AND METHOPRENE ON THE DEVELOPMENT AND METAMORPHOSIS OF POST- DIAPAUSE PUPA OF RICE STEM BORER SCIRPOPHAGA INCERTULAS WLK. (LEPIDOPTERA : PYRALIDAE) - ROYCHOUDHURY, N.; CHAKRAVORTY, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
Juvenoids hydroprene (Altozar or ZR-0512) and methoprene (Altosidor ZR-0515) when applied topically to 0-24-hr-old post-diapause pupae of rice stem borer Scirpophaga - incertulas WIk caused defective imaginal differentiation. Treated pupae developed either into defective adultoids which failed to emerge or, into adultoids which showed significant reduction of life span. There was no significant change in the duration of pupal life. Pre-emergence mortality was high in hydroprene treatments.